2002
DOI: 10.1128/jvi.76.9.4267-4274.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-Defective Gibbon Ape Leukemia Virus Vectors Can Be Rescued by Homologous but Not Heterologous Soluble Envelope Proteins

Abstract: Murine leukemia virus (MLV)-derived envelope proteins containing alterations in or adjacent to the highly conserved PHQ motif present at the N terminus of the envelope surface subunit (SU) are incorporated into vector particles but are not infectious due to a postbinding block to viral entry. These mutants can be rendered infectious by the addition of soluble receptor-binding domain (RBD) proteins in the culture medium. The RBD proteins that rescue the infectivity of these defective MLV vectors can be derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…2C). Taken together, these results indicate that HuPAR-2 plays a role in binding PERV-A that is analogous to the known multitransmembrane receptors for other gammaretroviruses (15)(16)(17).…”
Section: Identification Of Perv-a Receptorsmentioning
confidence: 59%
“…2C). Taken together, these results indicate that HuPAR-2 plays a role in binding PERV-A that is analogous to the known multitransmembrane receptors for other gammaretroviruses (15)(16)(17).…”
Section: Identification Of Perv-a Receptorsmentioning
confidence: 59%
“…Indeed, FeLV-B SUs can functionally substitute for FeLIX and mediate FeLV-T infection of cells expressing Pit1 (3). In our studies to date, we have found that only those cofactors with RBDs derived from enFeLV can facilitate infection by FeLV-T. Soluble SUs from amphotropic MLV (A-MLV), GALV, and FeLV-A are not able to facilitate infection in the same way, despite the fact that A-MLV can bind Pit2 and GALV can bind Pit1 (20,29). Unlike FeLV-B, which can utilize both Pit1 and Pit2, FeLV-T is specific in its requirement for Pit1 even when the dual-tropic FeLV-B SUs are supplied as cofactors (29).…”
mentioning
confidence: 93%
“…Many studies have revealed that the infectivity abolished by a DH mutation can be restored by the addition of a homologous or heterologous soluble SU or receptor-binding domain (RBD) that contains a complete PHQ motif in trans. This transactivation generally occurs more efficiently via a homologous RBD than a heterologous RBD, with the exception that porcine endogenous retroviruses were much more efficiently transactivated by a heterologous RBD derived from Gibbon ape leukemia virus (Lavillette & Kabat, 2004;Lavillette et al, 2000;Farrell et al, 2002;Lavillette et al, 2002).…”
Section: Introductionmentioning
confidence: 99%